DETERMINAN KEJADIAN STROKE PADA LANSIA (SCOOPING REVIEW) - Johannes Ginting; Agusman Halawa; Herbert Wau (Jurnal Keperawatan Priority, 2022)
The factors that cause stroke in the elderly, until now are still research that must be treated quickly, to minimize the mortality rate due to stroke events. The purpose of this study is to examine more deeply the factors triggering stroke in the elderly. This study uses the scoping review method. The inclusion criteria in the scoping review are articles published in databases of journals indexed in PubMed, Google Scholar, Science Direct, and ProQuest in English, with a cross-sectional design, case-control, Retrospective, and cohort. This journal was published in the period 2010 – 2021 so 12 articles that met the inclusion criteria were obtained. Results: The search results were 1,320 articles from 4 databases (PubMed, Google Scholar, Science Direct, and ProQuest) where 465 duplicate articles were deleted. Of the remaining 855 articles, 843 were excluded after screening for eligibility because they were irrelevant. The remaining 12 articles will be qualitatively analyzed using the NVIVO-12 plus application. Analysis shows that age, gender, smoking, and obesity are triggering factors for stroke in the elderly. The increase in risk factors for stroke in the elderly is due to increasing age prone to diseases (smoking and obesity) that are not controlled so that they will experience stroke events. On the other hand, non-compliance with preventive measures so that they have a low life expectancy due to the incidence of stroke. Smoking and obesity are high-risk for stroke because the blood vessels will narrow and cause blockages. So that more attention is paid to prevention and treatment to minimize the incidence of stroke as well as to improve the quality of life.